Migration and transnationalism : Pacific perspectives - Lee, Helen Morton, 1960-; Francis, Steve Tupai (Open Access e-Books, 2009)
"Pacific migration and transnationalism are addressed in this volume in the context of increasing globalisation and growing concerns about the future social, political and economic security of the Pacific region. As the case studies presented here show, the future of the Pacific depends in many ways on the ties diasporic Islanders maintain with their homelands."--Publisher's description